Pattern of Fascicular Involvement in Midportion Achilles Tendinopathy at Ultrasound. (September 2015) - Counsel, Peter; Comin, Jules; Davenport, Marcus; Connell, David
Background: The Achilles tendon is composed of fascicles from the soleus and gastrocnemius muscles, which are identifiable as discrete components at anatomical dissection. Hypothesis: The pattern of fascicular involvement in Achilles tendinopathy may be characterized at ultrasound, and this characterization is reliable between different observers. Study Design: Cross-sectional diagnostic study. Level of Evidence: Level 3. Methods: One hundred cases of Achilles tendinopathy were retrospectively evaluated by 2 blinded musculoskeletal radiologists. Using a short-axis anatomical map, each case was categorized as involving the fascicular territories of the medial head of gastrocnemius, lateral head of gastrocnemius, soleus, or combinations of these, or as indeterminate. Results: Both radiologists agreed on the fascicular involvement pattern in 93 of 100 cases; 20 involved only medial gastrocnemius territories, 8 lateral gastrocnemius, 15 soleus, 3 medial and lateral gastrocnemius, 21 medial gastrocnemius and soleus, 9 soleus and lateral gastrocnemius, and 16 the entire tendon, and 1 case was classified as indeterminate. In 7 cases, the interpretations were discordant. The kappa value was calculated as 0.92 (95% CI, 0.86-0.98) in keeping with a high level of interobserver agreement. Conclusion: As assessed at ultrasound, most cases of Achilles tendinopathy involve the medial head of gastrocnemius and/or soleus fascicles. Clinical Relevance: The provided observational data will increase understanding of patterns of Achilles tendinopathy.